1995
DOI: 10.1099/0022-1317-76-9-2311
|View full text |Cite
|
Sign up to set email alerts
|

Localization of cis-acting sequences essential for cymbidium ringspot tombusvirus defective interfering RNA replication

Abstract: The smallest defective interfering RNA (DI-2) of cymbidium ringspot tombusvirus (CyRSV) was used to identify the cis-acting sequences necessary for its replication by making a series of deletions throughout the 404 nt long molecule and testing the biological activity of mutants. Deletion or substitution of the conserved sequence blocks (A, B and C) always yielded inactive molecules. The deletion of only a few nucleotides could be tolerated beyond the natural deletion sites in blocks A and B. However, either ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 7 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…We also demonstrated that the poor target activity of short DI RNAs was not caused by either the low level of the DI RNAspecific guide RNAs or the size of the target molecule. Short DI RNAs, which contain almost exclusively cis -acting sequences required for replication (Havelda et al, 1995), may bind efficiently to the replicase complex and thus are not accessible to the RISC degradation complex of PTGS. Alternatively, the folding of DI RNAs may prevent PTGS-mediated degradation.…”
Section: Ptgs Selects For DI Rnas Containing Poor Ptgs Target Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that the poor target activity of short DI RNAs was not caused by either the low level of the DI RNAspecific guide RNAs or the size of the target molecule. Short DI RNAs, which contain almost exclusively cis -acting sequences required for replication (Havelda et al, 1995), may bind efficiently to the replicase complex and thus are not accessible to the RISC degradation complex of PTGS. Alternatively, the folding of DI RNAs may prevent PTGS-mediated degradation.…”
Section: Ptgs Selects For DI Rnas Containing Poor Ptgs Target Regionsmentioning
confidence: 99%
“…DI RNAs of Cymbidium ringspot tombusvirus (CymRSV) are among the most extensively studied DI RNA molecules. They are incapable of autonomous replication but contain all of the necessary cis -acting elements for replication (Havelda et al, 1995). During replication of CymRSV genomic RNA, a series of DI RNAs of ‫ف‬ 0.4 to 0.7 kb are generated de novo (Burgyán et al, 1991).…”
mentioning
confidence: 99%
“…DI RNAs are incapable of autonomous replication but contain all the necessary cis-acting elements for replication (Havelda et al, 1995). Trans-acting products required for CymRSV DI RNA replication are expressed from ORFs 1 and 2 of the CymRSV genome Kolla!…”
Section: Mutational Analysis Of Defective Interfering (Di)mentioning
confidence: 99%
“…1) (33,(45)(46)(47). These features are also common for DIs derived from other tombusviruses, such as Cymbidium ringspot virus (CymRSV) and Cucumber necrosis virus (CNV) (9,12,13,16,17).Regions I, II, and IV of DIs represent sequences essential for RNA amplification (3,33,45,49), and while region III is dispensable for DI replication of TBSV, it is required for CymRSV DI accumulation (3,17,33). The length of TBSV DI region III varies from 46 to 81 nucleotides (nt), depending on the DI isolate (3,20,47).…”
mentioning
confidence: 99%
“…The tombusvirus coat protein is translated from p41 on subgenomic RNA1 (sgRNA1), and P22 and P19 are expressed from p22 and p19 on sgRNA2 (21)(22)(23)36). TBSV P22 is required for cell-to-cell movement (7,10,42), and P19 is involved in host-specific systemic invasion and symptom development (6,38,41,42) and is active as a suppressor of gene silencing (31,32,44).Tombusviruses can serve as helper viruses for satellite RNAs (1, 2), and they are notorious for the accumulation of defective interfering RNAs (DIs) (13,17,20,24). DIs are spontaneous deletion mutants derived from the helper genome, and they are successfully amplified by trans-acting helper replicase proteins (20, 24).…”
mentioning
confidence: 99%